2021
DOI: 10.1186/s12902-021-00735-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of oxidative stress in the incidence of metabolic syndrome and obstructive sleep apnea

Abstract: Background Understanding the causes and risk factors of metabolic syndrome is important for promoting population health. Oxidative stress has been associated with metabolic syndrome, and also obstructive sleep apnea. These are two diseases which have common prognostic characteristics for heart disease. The aim of this study was to examine the role of oxidative stress in the concurrent presence of metabolic syndrome and obstructive sleep apnea in a working population. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The supplementation of CM and PECM was associated with increased activity of antioxidants such as SOD, catalase, and GPx (Table 3) even after 20 days of treatment in comparison to the control and other prebiotic groups. It is proven that higher levels of reactive oxygen species are strongly related to cellular dysfunction, resulting in several chronic diseases, including diabetes, MetS, and hypertension (Kargar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of CM and PECM was associated with increased activity of antioxidants such as SOD, catalase, and GPx (Table 3) even after 20 days of treatment in comparison to the control and other prebiotic groups. It is proven that higher levels of reactive oxygen species are strongly related to cellular dysfunction, resulting in several chronic diseases, including diabetes, MetS, and hypertension (Kargar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The products of this process are conjugated dienes (CD) and lipid peroxides (ROOH) [ 109 ], and also the so-called secondary products of lipid peroxidation, such as malondialdehyde (MDA), 4-hydroxy-2-nonenal (4-HNE) [ 110 ], and isoprostanes (IsoPs) [ 111 ]. It was shown that oxidative stress may take part in the etiopathogenesis of numerous systemic diseases, including CMDs such as CVD [ 16 , 86 , 97 ] and MetS [ 112 , 113 ].…”
Section: The Oxidant–antioxidant Balance and Oxidative Stressmentioning
confidence: 99%
“…Furthermore, obstructive sleep apnea is often observed in obese patients [ 89 ]. This pathology causes episodes of hypoxia/reoxygenation, which is also a cause of oxidative stress [ 90 ].…”
Section: Oxidative Stress and Obesitymentioning
confidence: 99%